(untitled) (Bangladesh Journal of Neuroscience, 2013)
Juvenile myasthenia gravis (JMG) is a rare autoimmune disorder of childhood. Pediatric presentation of MG is more common in Oriental than in Caucasian populations. JMG need to be differentiated from congenital myasthenia gravis which do not have haan autoimmune basis. An 11 years old girl presented with drooping of eye lids which was more marked at the later part of day and was gradually progressive . She had complained of double vision. She had no family history of myasthenia gravis. Ice pack test, repetitive nerve stimulation test, and anti acetylcholine receptor antibody test support the diagnosis. She was treated with pyridostigmine and was started as 30mg four times daily and increased to 60 mg/qds. Subsequently her symptoms improved gradually and she became stable. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 64-69